Covid-19 vaccination programme effectiveness against SARS-CoV-2 related infections, hospital admissions and deaths in the Apulia region of Italy: a one-year retrospective cohort study - Homan, Tobias; Mazzilli, Sara; Chieti, Antonio; Musa, Alessandra; Roth, Adam; Fortunato, Francesca; Bisceglia, Lucia; Prato, Rosa; Lopalco, Pier Luigi; Martinelli, Domenico (Scientific reports, 2022)
Studies reporting vaccine effectiveness against COVID-19 outcomes concentrate mainly on estimates of one single type of vaccine and variant, seldom considering waning effects. We aimed to estimate the effectiveness of the overall COVID-19 vaccination programme implemented in the Apulia region of Italy at preventing SARS-CoV-2 infections, COVID-19-related hospital admissions and deaths during alpha and delta variant dominant periods. We conducted a retrospective cohort study using electronic health records of persons 16 years and older resident in the Apulia region, assessing the effectiveness of the combined use of BNT162b2, mRNA-1273, ChAdOx1-S and Ad26.COV2.S vaccines against confirmed COVID-19 infections, hospitalisations and deaths, for fully and partially vaccinated persons as well as by time since vaccination and variants. Cox regression models yielding hazard ratios were used to calculate the overall vaccination programme effectiveness. From 1 January to 1 December 2021, we included 3,530,967 eligible persons in the cohort, of whom 2,770,299 were fully vaccinated and 158,313 were COVID-19 positive at the end of the study period. The effectiveness of the programme over the entire study period for fully vaccinated persons against COVID-19 infection, hospitalisation and death were 87.69% (CI95% 87.73–88.18), 94.08% (93.58–94.54) and 95.95% (CI95% 95.26–96.54), respectively. The effectiveness against COVID-19 infection of fully vaccinated subjects during the alpha and delta period was respectively 88.20% (CI95% 87.60–99.78) and 59.31% (CI95% 57.91–60.67), against hospitalisation 93.89% (CI95% 92.67–94.90) and 88.32% (CI95% 86.50–89.90) and against death 93.83% (CI95% 91.65–95.45) and 85.91 (CI95% 79.98–90.09). The waning effects of the programme regarding COVID-19 infection during the delta period were stronger than for alpha, with 75.85% (CI95% 74.38–77.24) effectiveness after 1–2 months and 8.35% (CI95% 3.45–13.01) after 5–6 months after full vaccination. The effectiveness against hospitalisation and death during the delta period waned rapidly and at 7–8-months after the full vaccination respectively decreased to 27.67% (CI95% 7.48–43.45) and 48.47 (CI95% 53.97–34.82). Our study suggests that the COVID-19 vaccination program in Apulia was strongly protective against COVID-19 infection, hospitalisation, and death due to alpha as well as delta variants, although its effectiveness is reduced over time.